Research on the Mechanism of China’s Energy Saving and Emission Reduction Policy on Green Innovation in Enterprises - Chai, Kuang-Cheng; Zhu, Jiawei; Lan, Hao-Ran; Jin, Chengsheng; Lu, Yujiao; Chang, Ke-Chiun (Frontiers in Environmental Science, 2022)
China's extensive growth since reforming and opening its economy has led to increased pollution, and under the United Nations Framework Convention on Climate Change, Chinese companies must initiate green innovation to meet the world trend and enhance their international competitiveness. In addition, with institutional and cultural differences, policy drive is a key focus of China's development. Therefore, China's Energy Saving and Emission Reduction policy has its own necessity and characteristics as a mechanism for green innovation in enterprises. This study examines the impact of the 13th Five-Year Plan on green innovation from the perspective of the Energy Saving and Emission Reduction policy. First, the data of 100 listed enterprises in two control zones (TCZ) and non-two control zones (non-TCZ) from 2014 to 2019 were selected to identify whether the implementation of the policy has an impact on the innovation of heavily polluting enterprises using the double difference method (DID). The study found that the 13th Five-Year Plan for Energy Saving and Emission Reduction had a negative impact on the innovation of heavily polluting enterprises. Further, the study found that the policy had a negative impact on enterprises’ innovation through the transmission channel of increasing the environmental cost of enterprises, thus reducing investment on research and development (R&D). It is suggested that the state should start with the policy itself, identify its precise target, and formulate flexible environmental regulation policies.